The Influence of Tilt Angle of 120 WP Solar Panels on Light Intensity and Generated Electrical Power - Masthura Masthura; Abdul Halim Daulay (Elkawnie: Journal of Islamic Science and Technology, 2024)
Abstract: In designing solar panel devices, generally the tilt angle of the panel surface is designed with a static design and this greatly influences the results of the electricity source generated. The design of the tool is intended to be in coordinates that are perpendicular to the direction of the sunlight rays so that it receives maximum solar radiation. This research aims to determine the relationship between the tilt angle of the solar panels and the light intensity and electrical power generated and to determine the optimal tilt angle of the solar panels based on the values of light intensity and electrical power. The indicators measured consist of light intensity, voltage, current and electrical power by varying the tilt angle of the solar panel. The results of this research show that the tilt angle of the solar panel greatly influences the measured light intensity value so that the greater the light intensity obtained, the higher the output voltage of the solar panel. The most optimal tilt angle is at an angle of 105o and 120o with the greatest light intensity so that the resulting output power is correspondingly greater.Abstrak: Dalam merancang alat panel surya, pada umumnya posisi kemiringan dari permukaan panel dirancang dengan desain statis sangat mempengaruhi hasil dari sumber listrik yang dihasilkan. Rancangan alat  diupayakan  berada di koordinat yang  tegak lurus dengan arah pancaran cahaya matahari agar menerima radiasi matahari yang maksimal. Penelitian ini bertujuan untuk mengetahui hubungan posisi kemiringan panel surya terhadap intensitas cahaya dan daya listrik yang dihasilkan serta mengetahui posisi kemiringan panel surya yang optimal berdasarkan nilai intensitas cahaya dan daya listriknya. Indikator yang diukur terdiri dari intensitas cahaya, tegangan, arus, dan daya listrik  dengan memvariasikan posisi kemiringan dari panel surya. Hasil penelitian ini menunjukkan posisi kemiringan sebuah panel surya sangat mempengaruhi  nilai intensitas cahaya yang diukur sehingga semakin besar intensitas cahaya yang didapat maka tegangan keluaran panel surya mengalami kenaikan. Posisi kemiringan yang paling optimal pada sudut 105o dan 120o dengan intensitas cahaya yang didapat terbesar sehingga daya keluaran yang dihasilkan sejalan yaitu semakin besar pula.